FAKTOR YANG MEMPENGARUHI HUBUNGAN PENGETAHUAN IBU NIFAS DENGAN PERAWATAN LUKA SECTIO CAESAREA - Elyani Sembiring; Dewi Astuti Pasaribu; Martina Hutahaean (Jurnal Ilmiah Keperawatan IMELDA, 2025)
Caesarean section (SC) is an artificial delivery in which the fetus is delivered through an incision in the abdominal wall and uterus, which can cause bleeding and incision wounds. Caesarean section causes an incision wound in the abdomen. Many factors influence the healing process of caesarean section wounds. One factor that can influence this is nutrition, age, education, source of information, and occupation. The level of patient knowledge about wound care is an important factor in reducing the incidence of surgical site infections in SC patients. The purpose of this study was to determine the factors that influence the level of knowledge of postpartum mothers about SC (sectio caesarea) wound care at Estomihi Medan Hospital. This study used Analytical method with Cross Sectional Approach. The population in this study amounted to 87 respondents, namely postpartum mothers of sectio caesarea with a sample size of 47 respondents. Data collection using a questionnaire. The results of the chi-square test obtained a P-Value factor value of 0.000 <0.05, which means that there is a relationship between the Knowledge Factors of postpartum mothers about Sectio Caesarean Wound Care at Estomihi Medan Hospital.